Study of the rowing technique major components - Kolumbet, N.; Babina, N.; Babina, G.; Dudorova, L. Y.; Natroshvili, S. G. (Journal of Physical Education and Sport, 2018)
The aim of the work: determining the major characteristics of the rowing technique motor structure. Ìàterial and methods. Twenty rowers (first-class athletes) specialized in sculling participated in studies. Athletes covered 200 m distance and the control 500 m segment at different speed and pace. Results. The most important index of the rowing technique at any pace is the impulse of force of water pressure on the oar blade (kg·s-1). Correlation coefficients constitute: at a pace of 22-24 strokes·min-1 . r=0,93 (at P<0,001), at a pace of 28-30 strokes·min-1 . r=0,96 (at P<0,001) and at a pace of 34-35 strokes·min-1 . r=0,83 (at P<0,001). Achievement of high result necessitates the development in athletes of the ability to maintain high impulse of force for the speed (close to distance) of the boat. In addition, this characteristic should be developed under conditions of muscle fatigue, competitive excitement, in high winds, high seas, etc. Acceleration of the general center of gravity of rower`s body at the approach has a positive impact on sports result at any pace of rowing. Conclusions. The impulse of force of water pressure on the oar blade represents the main component of the rowing technique efficiency. The way of the boat steadiness is the second criterion of the rowing technique efficiency, whereas the acceleration of the general center of gravity of rower`s body at the approach constitutes the third component of the rowing technique efficiency.